2022
DOI: 10.3390/app12031086
|View full text |Cite
|
Sign up to set email alerts
|

Performance Prediction of Underwater Acoustic Communications Based on Channel Impulse Responses

Abstract: Predicting the channel quality for an underwater acoustic communication link is not a straightforward task. Previous approaches have focused on either physical observations of weather or engineered signal features, some of which require substantial processing to obtain. This work applies a convolutional neural network to the channel impulse responses, allowing the network to learn the features that are useful in predicting the channel quality. Results obtained are comparable or better than conventional supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In [71], a one-dimensional CNN was employed for predicting the performance of UWA communications based on CIR. Two datasets were used in the experiments, and the results demonstrated that the predictive performance of the CNN was superior to traditional machine learning methods on any of the datasets.…”
Section: Algorithm 7 Lstm Prediction Algorithmmentioning
confidence: 99%
“…In [71], a one-dimensional CNN was employed for predicting the performance of UWA communications based on CIR. Two datasets were used in the experiments, and the results demonstrated that the predictive performance of the CNN was superior to traditional machine learning methods on any of the datasets.…”
Section: Algorithm 7 Lstm Prediction Algorithmmentioning
confidence: 99%
“…Using a computation template, create characteristic maps from each target region that are the same size. After that, get a Support Vector Machine (SVM) [11] and find all the potential regions' category entries. For every screen that qualifies, this R-CNN approach uses algebraic image distortion to determine the inputs of a completely Convolutional with a constant size, regardless of its appearance.…”
Section: Related Workmentioning
confidence: 99%
“…Channel modeling is important for the estimation of transmission quality. In [11] and [12], the authors present methods of underwater channel modeling. The channel impulse response can also be utilized for the estimation of underwater platform motion parameters [13].…”
Section: Introductionmentioning
confidence: 99%